(untitled) (Yearbook - Faculty of Economics, 2013)
In paper are present some aspects to new approaches to the leadership as one of the basic factor for determining the organization culture in organizations. Also some results of empirical researches on cca. 400 tested persons in 34 organizations in Republic of Macedonia are presented.The real leadership means that the ability of an individual to infl uence, motivate and enable others to contribute toward the effectiveness and success of the organization of which they are membres. Special attention is given to theories of transactional, transformational an charismatic leadership, with accent to their importance in contemporary study of leadership in organizations. Also it points to the increasing importance of the discipline of organizational behavior, which is devoted, as an interdisciplinary fi eld of study, to better understanding and managing human side of the work.